Silent Tears of Midwives: 'I Want Every Mother Who Gives Birth to Have Her Baby Alive'-A Narrative Inquiry of Midwives Experiences of Very Early Neonatal Death from Tanzania - Jan Becker; Chase Becker; Rachel Abeysekera; James Moir; Marion Gray; Meshack Shimwela; Florin Oprescu (MDPI AG, 2023)
Background: Midwives working in settings with limited clinical resources experience high rates of very early neonatal deaths. Midwives manage the impact of this grief and trauma almost daily, which may affect patient care and their own well-being. Research Aims: To explore how midwives are impacted by and cope with high rates of very early neonatal deaths. To document midwives' insights and local solutions that may reduce very early neonatal deaths in limited resource settings. To document the stories of midwives in order to create awareness and garner support for midwives and their critical work in low resource settings. Methods: Narrative inquiry utilizing semi structured interviews. Twenty-one midwives with at least six months experience who had experienced or witnessed very early neonatal death were interviewed. Data were audio recorded and transcribed, and reflexive thematic analysis of transcripts was conducted. Results and Discussion: Three themes were identified: (1) deep sadness resulting from very early neonatal deaths leading to internal struggles; (2) use of spirituality, including prayer and occasional beliefs that unexplainable deaths were 'God's plan'; and (3) development of resilience by seeking solutions, educating themselves, taking accountability and guiding mothers. Participating midwives noted that inadequate staff and high caseloads with limited basic supplies hindered their clinical practice. Participants articulated that they concentrated on active solutions to save babies during labour, such as vigilant foetal rate heart monitoring and partogram. Further, reduction and prevention of very early neonatal death is a complex problem requiring multidisciplinary teams and woman-centred care approaches to address issues contributing to the health of mothers and their new-borns. Conclusions: Midwives' narratives highlighted ways of coping with grief and deep sadness, through prayer, and further education of both mothers and fellow colleagues to achieve better antenatal and intrapartum care and outcomes. This study gave midwives an opportunity for their voices to be heard and to generate solutions or insights that can be shared with colleagues in similar low-resource settings.